A Review on Applications of Nanobots in Combating Complex Diseases - Rifat, Tashnuva; Hossain, Md Shahadat; Alam, Md Mahbubul; Rouf, Abu Shara Shamsur (Bangladesh Pharmaceutical Journal, 2019)
In the current years, a lot of research works have been continued in the quest to find a desired drug delivery system within the human body. Among different drug delivery systems, nanobots have become much popular due to its capability to perform different tasks like actuating, sensing, signaling, information processing and intelligence at nanoscale dimension. A nanobot is a robotic machine that can be programmed to diagnose, monitor and treat various vital diseases. It works at cellular level with minimum side effects and thus substitute the conventional treatment procedures. The major limitations of nanobots are proper designing and manufacturing process. In spite of its expensive manufacturing set up, they are pre-eminent for medical applications, such as nanobots like respirocytes, microbivores and clottocytes have been designed to act as artificial substitutes of blood. This article describes the use of nanobots in different fields of medical science like diagnosis and treatment of cancer, diabetes, aneurysm, tetanus, HIV, skin disease, gout as well as in the field of dentistry, surgery and treating many other diseases. It also represents the recent research which has been applied in vivo to different animals. Scientists hope that nanobots will act on molecular level, protect the biological system and thus ensure a better and longer life. Bangladesh Pharmaceutical Journal 22(1): 99-108, 2019